Intervensi Yang Efektif Untuk Mengurangi Kecemasan Keluarga Pasien ICU - Rizky Aulia Ramadhan; Tina Handayani Nasution; Ifa Hafifah (Universitas Pekalongan, 2022)
ABSTRACTBackground: Intensive Care Unit (ICU) that a ward for treat critical ill patients. The treatment for patients in ICU has a physical and psychological impact on the family, one of which is anxiety. The anxiety requires effective intervention to reduce it. Objectives: To determine the types of effective interventions, duration of implementation, and implementation techniques to reduce family anxiety of ICU patients. Methods: This study was a literature review. Ten literatures were identified from three databases sources such as Google Scholar, Proquest, and Science Direct in the range of publication 2016-2021. The research design was a quasi-experimental study with adult ICU patients as population. Articles analysis was carried out using the JBI Critical Appraisal Checklist for Quasi-Experimental Studies. Results: All interventions were influential and effective in reducing family anxiety of ICU patients. There are 10 kinds of interventions that can be used to reduce family anxiety of ICU patients. Discussion: There are ten effective interventions to reduce family anxiety of ICU patients including spiritual welfare provision, yoga, aurosoma therapy, spiritual therapy, health education about critical care, education, nurse therapeutic communication, consultation activities, spiritual counseling, and religious and spiritual. Only 5 out of 10 articles mention the duration of the intervention.Keywords: ICU, Intensive Care Unit, anxiety, family ABSTRAKLatar Belakang: Intensive Care Unit (ICU) adalah ruangan khusus untuk menangani pasien kritis. Perawatan pasien di ICU menimbulkan dampak fisik dan psikologis bagi keluarga salah satunya adalah kecemasan. Tingginya angka kecemasan diperlukan intervensi yang efektif untuk menguranginya. Tujuan: Mengetahui jenis intervensi yang efektif, durasi pelaksanaan, dan teknik pelaksanaan untuk mengurangi kecemasan keluarga pasien ICU. Metode: Studi ini dilakukan dengan literature review. Sepuluh literatur diidentifikasi dari tiga data base yaitu: Google Scholar, Proquest, dan Science Direct dalam rentang tahun 2016-2021. Desain penelitian artikel yang ditelaah adalah Quasi eksperimental studi. Semua artikel dianalisis menggunakan intrumen JBI Critical Appraisal Checklist for Quasi-Experimental Studies. Hasil: Seluruh intervensi berpengaruh dan efektif dalam mengurangi kecemasan keluarga pasien ICU. Terdapat 10 macam intervensi yang dapat digunakan untuk mengurangi kecemasan keluarga pasien. Pembahasan: Terdapat sepuluh intervensi yang efektif untuk mengurangi kecemasan keluarga pasien ICU diantaranya pembekalan kesejahteraan spiritual, yoga, terapi aurosoma, spiritual terapi, pendidikan kesehatan tentang peraatan kritis, edukasi, komunikasi terapeutik perawat, kegiatan konsultasi, konseling spiritual, dan religious dan spiritual. Hanya 5 dari 10 artikel yang menyebutkan durasi melakukan intervensi.Kata Kunci: ICU, Intensive Care Unit, kecemasan, keluarga